2022
DOI: 10.1093/oncolo/oyac040
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Desert Tumor Microenvironment in Thoracic SMARCA4-Deficient Undifferentiated Tumors with Limited Efficacy of Immune Checkpoint Inhibitors

Abstract: Background Thoracic SMARCA4-deficient undifferentiated tumors (SMARCA4-UT) are aggressive neoplasms. Data linking BAF alterations with tumor microenvironment (TME) and efficacy of immune checkpoint inhibitors (ICI) are contradictory. The TME of SMARCA4-UT and their response to ICI are unknown. Materials and Methods Patients diagnosed with SMARCA4-UT in our institution were included. Immunostainings for tertiary lymphoid struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Furthermore, it can influence the outcome and effectiveness of cancer management therapies. Gantzer et al identified nine SMARCA4-UT patients and eight patients had no tertiary lymphoid structures, consistent with an immune desert TME phenotype ( 26 ). In this case, next-generation sequencing was performed and immunotherapy combined with chemotherapy was selected.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, it can influence the outcome and effectiveness of cancer management therapies. Gantzer et al identified nine SMARCA4-UT patients and eight patients had no tertiary lymphoid structures, consistent with an immune desert TME phenotype ( 26 ). In this case, next-generation sequencing was performed and immunotherapy combined with chemotherapy was selected.…”
Section: Discussionmentioning
confidence: 90%
“… 3 , 9 Recent studies have found that most patients with SMARCA4-UT exhibit an immune desert tumor microenvironment, limited efficacy for immune checkpoint inhibitors, and poor prognosis. 9 , 10 Currently, most patients with SMARCA4-UT are not suitable for molecularly targeted therapies because few targetable alterations have been identified. The young woman in our case was a nonsmoker who may have a higher incidence of ALK rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Renamed as “SMARCA4‐deficient undifferentiated tumor,” this tumor type distinctly differs from SMARCA4‐deficient NSCLC in phenotype 14 . Subsequent studies described SMARAC4‐UTs as highly aggressive tumors that predominantly occur in male patients with younger age and heavy smoking history 17,23,24 . Despite this, the response of SMARCA4‐UTs to PD‐1 inhibitors remains inconsistently reported and underexplored 23,24 .…”
Section: Discussionmentioning
confidence: 99%